Paciente femenino de 51 años de edad con tiroiditis de Hashimoto - Pazo Urrutia, Wilson Eloy (2018)
Hashimoto's Thyroiditis is due to the elevated TSH level and the levels of the thyroid hormones decreased in some cases, the clinical syndrome is usually characterized by enlarged goiter in the front of the neck. The clinical case presented is a female patient of 51 years of age with Hashimoto's Thyroiditis, she was diagnosed 4 years ago, which does not have an adequate treatment, so the TSH level has not been controlled; it was verified by laboratory tests. Through a nutritional and pharmacological treatment, we will decrease and maintain the plasma levels of triglyceride lipids and the hormone TSH, the patient will be prescribed a hypo-fat hypo-sodium diet that will be activated in four meals a day. It is recommended to perform a light exercise of 30 minutes a day, during 20 days by means of its adaptation it will increase its physical exercises in this way improving the health of the patient so much alimentary, physically and emotionally